BIAS GENDER DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER: Kajian Feminisme - Winda Fatmalia A; Harris Effendi Thahar; Nurizzati Nurizzati (Jurnal Bahasa dan Sastra, 2012)
The purposes of this study were to (1) describe drifting off gender that is looked in women figurates in Bumi Manusia novel of Pramoedya Ananta Toer. This observation data is a quotation or a sentence that expert in drifting off gender, espesially is houched with woman figure that is found in Bumi Manusia novel. The source of data in this observation is Bumi Manusia novel of Pramoedya Ananta Toer, that created by Lentera Dipantara on 2010. The data is collected according to describtive with such steps: reading, indicating, noting down, and to investigate the data. The analysis of data is done, with such steps: describing, analyzing, interpreting, and concluding the result of the observasion. Invention of the observation is first, the women figure in Bumi Manusia novel is formed of main figure and close figure. Second, to drift off gender that is realized by woman figure exist of marginalisation, subordination, stereotype, hardness, and double burden work.